Hubungan Pengetahuan dan Sikap Orang tua dengan Penggunaan Baby Walker Pada Bayi Usia 8-12 Bulan di Klinik Khadijah - Suliasni, Natasya Putri; Hulu, Nente Sugianti; Sitepu, Nika Ayu Adelia Br; Siregar, Debi Novita (Universitas Malahayati, 2024)
ABSTRACT Every family wants to give birth to healthy, intelligent children who will become the next generation who will be useful for their parents, nation and state. One effort to achieve this is by providing children with proper care which will help children achieve their optimal abilities, so parents must provide appropriate stimulation for their children so that the development of language, motor skills, socialization and independence of toddlers is appropriate to their age. Baby walkers are known as tools to help toddlers walk which are designed to be safe and independent. The knowledge and attitudes of working parents also influence children’s development, both having a positive and negative impact on the use of baby walkers for babies aged 8-12 months. Todetermine the relationship between parental knowledge and attitudes and the use of Baby Walkers in babies aged 8-12 months at the Khadijah Clinic in 2023. This research uses analytical observational research using correlation study research methods which aims to determine the relationship between people'sknowledge and attitudes. old age on walking ability in children aged 8-12 months.In this design a cross sectional approach is used. Data collection used questionnaires and interviews. The results of the chi-square test obtained ap value = 0.000 < 0.05, this shows that there is a relationship between parental knowledge and attitudes and the use of Baby Walkers in babies aged 8-12 months at the Khadijah Clinic in 2023. Keywords: Knowledge, Attitude, Parent, Baby Walker, Baby ABSTRAK Setiap keluarga pasti ingin melahirkan anak yang sehat, cerdas dan menjadi generasi penerus yang berguna bagi orang tua, bangsa dan negara. Salah satu upaya untuk mencapai hal tersebut adalah dengan memberikan pengasuhan yang tepat pada anak yang akan membantu anak mencapai kemampuan optimalnya, sehingga orang tua harus memberikan stimulasi yang tepat bagi anaknya agar perkembangan bahasa, motorik, sosialisasi dan kemandirian balita sesuai dengan usianya. Baby walker dikenal sebagai alat untuk membantu balita berjalan yang didesain agar aman dan mandiri. Pengetahuan dan sikap orang tua yang bekerja juga berpengaruh terhadap perkembangan anak, baik yang berdampak positif maupun negatif terhadap penggunaan baby walker pada balita usia 8-12 bulan. Tujuan penelitian ini adalah untuk mengetahui hubungan antara pengetahuan dan sikap orang tua dengan penggunaan baby walker pada bayi usia 8-12 bulan di Klinik Khadijah pada tahun 2023. Penelitian ini menggunakan jenis penelitian observasional analitik dengan menggunakan metode penelitian studi korelasi yang bertujuan untuk mengetahui hubungan pengetahuan dan sikap orang tua terhadap kemampuan berjalan pada anak usia 8-12 bulan. Pengumpulan data menggunakan kuesioner dan wawancara. Hasil uji chi-square diperoleh nilai p = 0,000 < 0,05, hal ini menunjukkan bahwa ada hubungan antara pengetahuan dan sikap orang tua dengan penggunaan Baby Walker pada bayi usia 8-12 bulan di Klinik Khadijah tahun 2023. Kata Kunci: Pengetahuan, Sikap, Orang Tua, Baby Walker, Bayi